Molecular Epidemiology of Penicillin-Resistant Streptococcus pneumoniae Isolates Recovered in Italy from 1993 to 1996 - Marchese, Anna (American Society for Microbiology, 1998)
Thirty-nine penicillin-resistant Streptococcus pneumoniae isolates recovered among the approximately 700 pneumococcal strains collected from 1993 to 1996 in central and northern Italy were analyzed for several characteristics, including serotype, antibiotic susceptibility profile, chromosomal relatedness (by using pulsed-field gel electrophoresis [PFGE]), restriction fragment length polymorphism (RFLP) of the penicillin-binding protein (PBP) genes 1A, 2X, and 2B, and the presence of a variety of antibiotic resistance genes (determined by hybridization with appropriate DNA probes). The MICs of penicillin for most of the isolates (30 of 39) were high, in the range of 1 μg/ml or higher, and these 30 isolates carried additional resistance traits to two or more drugs (erythromycin, chloramphenicol, co-trimoxazole, and tetracycline) and expressed serotypes 9, 19, and 23 and three distinct PFGE patterns. More than half (22 of 30) of the isolates for which MICs were high were identified as representatives of two widespread international epidemic clones of S. pneumoniae. The first one of these clones (seven isolates) expressed serotype 23F and possessed all properties characteristic of the widespread Spanish/USA international clone. Seven additional strains with serotype 19 also had the same PFGE pattern, PBP gene, and RFLP polymorphisms, and other properties typical of the serotype 23 Spanish/USA clone, suggesting that these strains were the products of a capsular transformation event (from serotype 23F to serotype 19) in which the Spanish/USA clone was the recipient. The second international clone was represented by eight serotype 9 isolates which were resistant to penicillin and trimethoprim-sulfamethoxazole and had the molecular properties of the French/Spanish epidemic clone. The remaining eight isolates for which penicillin MICs were high appeared to represent a hitherto-undescribed “Italian” clone; they had a novel PFGE type, unique RFLPs for the PBP genes, and resistance to tetracycline, trimethoprim-sulfamethoxazole, and erythromycin, and the penicillin MICs for these isolates were 2 to 4 μg/ml.